DAMPAK PERMAINAN ENGKLEK MODIFIKASI DALAM MENGEMBANGKAN MOTORIK KASAR ANAK DI TAMAN KANAK - KANAK - Indri Noviardi; Nurhafizah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article was written based on the results of research which was motivated by children's gross motor skills not being in accordance with the characteristics that children aged 5-6 years should have. This study aims to determine the effect of the modified engklek game on children's gross motor skills at Al Azhar 32 Padang Islamic Kindergarten. The method used is an experimental method with a quantitative approach in the form of a Quasi Experiment. The population of this study were all children at Al Azhar Islamic Kindergarten 32 Padang, with a sample of class B Makkah as the experimental class and B Mina as the control class. Data analysis techniques use normality tests, homogeneity tests and hypothesis tests. To test the quality of the research instrument, validation was carried out with expert experts and statistical calculations. Hypothesis testing was carried out using the T test statistical technique which showed a significance level of 0.001. The results of this research were seen during the pre-test in the experimental class 240 with an average of 12.63 and in the control class 214 with an average of 11.26. Meanwhile for the post test in the experimental class there were 431 with an average of 22.68 and in the control class there were 354 with an average value of 18.63. Thus, after statistical calculations were carried out there were differences between the experimental class and the control class. Where the post test results in the experimental class were higher than the control class with a difference of 4.05.  Based on these results, it can be concluded that the modified engklek game is significant in improving the gross motor development of children aged 5-6 years at Al Azhar Islamic Kindergarten 32 Padang.